THE POTENTIAL OF GUAVA LEAF (Psidium guajava L.) FOR DIARRHEA - Fratiwi, Yolanda (Majority, 2015)
Abstract Diarrhea is one of the health problems which is still being the most crusial effect that causes the morbidity and mortality of children in developing country including in Indonesia. Most of patients with diarrhea are treated with rehydration and continued with symptomatic and causative treatment. In causative treatment, antibiotic is used to kill the microorganism as the cause of diarrhea itself. Nowdays, the treatment is mostly done with oral antibiotics that are found in pharmacies with expensive cost relatively and it can cause side effects for diarrhea patients. Another alternative treatments are traditional medicines that easily available advantages and relatively cheap. Herbal plants is widely used to alternative medicines among the community. The one of plants that have been used as antidiarrheal is guava (Psidium guajava L.), especially guava leaf. Active compounds in guava leaf that serves as antidiarrheal is flavonoid especially quercetin flavonoid that can inhibit the release of acetylcholine and intestinal contraction, tannins that has the effect of reducing intestinal peristaltic, essential oils and alkaloids are microorganism killer and growth inhibitors in the intestines. Psidium guajava L. leaf extract can be used as an alternative treatment of diarrhea. Keywords: diarrhea, Psidium guajava L. leaf, quercetin, tannin Abstrak Diare merupakan salah satu masalah kesehatan yang masih menjadi penyebab utama tingginya morbiditas dan mortalitas pada anak di negara berkembang termasuk di Indonesia. Upaya penatalaksanaan pada penderita diare sebagian besar dengan rehidrasi dan dilanjutkan dengan pengobatan simtomatik dan pengobatan kausatif. Untuk pengobatan kausatif mikroorganisme penyebab diare dimatikan dengan menggunakan antibiotik. Pengobatan modern yang banyak dilakukan adalah dengan pemberian antibiotik oral yang banyak ditemukan di apotek dengan biaya yang relatif mahal dan dapat menyebabkan efek samping bagi penderita diare. Alternatif pengobatan lain adalah dengan obat tradisional yang mempunyai keuntungan mudah diperoleh dan relatif murah. Tanaman herbal banyak digunakan sebagai alternatif pengobatan di kalangan masyarakat. Salah satu tanaman yang telah digunakan sebagai antidiare adalah jambu biji (Psidium guajava L.), terutama bagian daun. Senyawa aktif dalam daun jambu biji yang berfungsi sebagai antidiare adalah flavonoid khususnya quercetin yang dapat menghambat pengeluaran asetilkolin dan kontraksi usus, tanin yang memiliki efek mengurangi peristaltik usus, minyak atsiri dan alkaloid yang merupakan inhibitor pertumbuhan dan mematikan mikroorganisme di usus. Ekstrak daun Psidium guajava L. dapat dijadikan sebagai alternatif pengobatan diare. Kata kunci: daun Psidium guajava L., diare, quercetin, tanin